Pengaruh Model PJBL Berbasis Deep Learning dan ICT terhadap Kemampuan Berfikir Kritis Siswa Kelas V pada Pembelajaran Pendidikan Pancasila - Eriska Rahmawati; Kahirun Nisa; Muhammad Erfan (Mataram University, 2026)
This study aims to examine the effect of the Project Based Learning (PjBL) model integrated with deep learning and ICT on fifth-grade students' critical thinking skills in Pancasila Education. The novelty lies in the simultaneous integration of these three components at the elementary school level, which remains rarely explored. The urgency is grounded in the initial finding that only 27.78% of students demonstrated adequate critical thinking, alongside low national AKM scores in reasoning indicators. A quantitative approach with a quasi-experimental method and nonequivalent control group design was employed. The entire population of 71 fifth-grade students at SDN 44 Ampenan was taken (saturated sampling), with class VA as the control and class VB as the experimental group. Data were collected through essay tests (pretest-posttest) and observation sheets after validity and reliability tests. Analysis included normality, homogeneity, independent sample t-test, and effect size. The results show that the PjBL model based on deep learning and ICT significantly outperforms conventional learning. The experimental group's mean posttest score reached 82.04, while the control group scored only 73.74. The hypothesis test yielded a significance of 0.001 (<0.05), rejecting H₀. In the brief discussion, the model's effectiveness is explained through the synergy between PjBL syntax, deep learning approaches (mindful, meaningful, joyful), and ICT support (Canva, interactive videos), which progressively train critical thinking indicators such as analysis, evaluation, and decision-making. The improvement in learning implementation from 86.30% to 98.45% over four meetings indicates good adaptability. The effect size of 2.33 (very large) confirms that the treatment effect is not only statistically significant but also has an extraordinary practical impact. Therefore, the PjBL model based on deep learning and ICT is proven effective and recommended as an instructional innovation to improve students' critical thinking skills in Pancasila Education, while addressing the challenges of low literacy and reasoning in the digital era.